2020
DOI: 10.1371/journal.pone.0233646
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial diversity, inflammation, and oxidative stress are associated with tacrolimus dosing requirements early after heart transplantation

Abstract: Introduction Effective tacrolimus (TAC) dosing is hampered by complex pharmacokinetics and significant patient variability. The gut microbiome, a key mediator of endotoxemia, inflammation and oxidative stress in advanced heart failure (HF) patients, is a possible contributor to interindividual variations in drug efficacy. The effect of alterations in the gut microbiome on TAC dosing requirements after heart transplant (HT) has not been explored. Methods We enrolled 24 patients (mean age = 55.8 ±2.3 years) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Association of TAC and change in oxidative stress marker 8,12-iso-isoprostane F-2alpha-VI has been described previously in heart transplant patients [ 17 ]. Oxidative stress and mitochondrial dysfunction has also been reported in an in vitro organoid model of nephrotoxicity in TAC-induced renal injury characterized by oxidative stress and production of inflammatory cytokines [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 89%
“…Association of TAC and change in oxidative stress marker 8,12-iso-isoprostane F-2alpha-VI has been described previously in heart transplant patients [ 17 ]. Oxidative stress and mitochondrial dysfunction has also been reported in an in vitro organoid model of nephrotoxicity in TAC-induced renal injury characterized by oxidative stress and production of inflammatory cytokines [ 9 , 18 ].…”
Section: Introductionmentioning
confidence: 89%
“…To our knowledge, no studies have been conducted investigating the effect of tacrolimus or cyclosporine A on the microbiota in IBD patients. However, in patients after heart transplantation, a higher diversity and an increased abundance of several bacterial taxa, such as Lachnospiraceae, Blautia, and Roseburia, were found in the higher dose (median dose 0.18 mg/kg/day) as compared to an increase in a taxon belonging to Bacteroides in the low dose (0.07 mg/kg/day) tacrolimus group (Jennings et al, 2020). However, many if not all patients used co-medication (Jennings et al, 2020), of which some can influence the intestinal microbiota, such as proton pump inhibitors (Imhann et al, 2017).…”
Section: Impact Of Calcineurin Inhibitors On the Intestinal Microbiotamentioning
confidence: 90%
“…However, in patients after heart transplantation, a higher diversity and an increased abundance of several bacterial taxa, such as Lachnospiraceae, Blautia, and Roseburia, were found in the higher dose (median dose 0.18 mg/kg/day) as compared to an increase in a taxon belonging to Bacteroides in the low dose (0.07 mg/kg/day) tacrolimus group (Jennings et al, 2020). However, many if not all patients used co-medication (Jennings et al, 2020), of which some can influence the intestinal microbiota, such as proton pump inhibitors (Imhann et al, 2017). Furthermore, the at least 4-fold higher plasma trough levels even in the low-dose group makes these data difficult to compare with the IBD patient group.…”
Section: Impact Of Calcineurin Inhibitors On the Intestinal Microbiotamentioning
confidence: 90%
“…In the group needing escalation of tacrolimus dosing to maintain the target drug concentration, Feacalibacterium prausitzii represented 11.8% of the gut microbiota compared with 0.8% in the drug stable group one week after transplantation [ 34 ]. Similarly, Jennings et al found a relationship between gut microbiota diversity and tacrolimus dosing requirements in patients early after heart transplantation [ 35 ]. On the other hand, Woodworth et al reviewed 10 cases of solid organ transplantation patients and found non-significant differences in tacrolimus dosing after FMT for treatment of CDI.…”
Section: Does the Microbiota Prolong Renal Graft Function?mentioning
confidence: 99%